2021
DOI: 10.1002/acn3.51305
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament levels and patient‐reported outcomes in multiple sclerosis

Abstract: Objective Serum neurofilament light (sNfL) is a promising new biomarker in multiple sclerosis (MS). We explored the relationship between sNfL and health outcomes and resource use in MS patients. Methods MS patients with serum samples and health‐outcome measurements collected longitudinally between 2011 and 2016 were analyzed. sNfL values were evaluated across age and gender. Data were analyzed using correlation with log‐transformed sNfL values. Results A total of 304 MS patients with a mean age of 32.9 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
9
4
Order By: Relevance
“…According to cross-sectional studies, high baseline CSF NfL levels correlate with high baseline EDSS [ 156 , 285 ] and future EDSS progression [ 276 , 288 , 290 ]. Somewhat contradictory to this data are the results of other studies that confirmed the correlation between baseline CSF [ 298 ], serum [ 289 ] and plasma [ 313 ] NfL levels and baseline EDSS but failed to link them to future EDSS and disability progression. Some studies documented a link between baseline serum NfL and baseline EDSS [ 243 , 269 , 289 , 297 , 311 ], while others did not find such a correlation [ 314 , 315 , 316 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosiscontrasting
confidence: 65%
See 2 more Smart Citations
“…According to cross-sectional studies, high baseline CSF NfL levels correlate with high baseline EDSS [ 156 , 285 ] and future EDSS progression [ 276 , 288 , 290 ]. Somewhat contradictory to this data are the results of other studies that confirmed the correlation between baseline CSF [ 298 ], serum [ 289 ] and plasma [ 313 ] NfL levels and baseline EDSS but failed to link them to future EDSS and disability progression. Some studies documented a link between baseline serum NfL and baseline EDSS [ 243 , 269 , 289 , 297 , 311 ], while others did not find such a correlation [ 314 , 315 , 316 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosiscontrasting
confidence: 65%
“…Somewhat contradictory to this data are the results of other studies that confirmed the correlation between baseline CSF [ 298 ], serum [ 289 ] and plasma [ 313 ] NfL levels and baseline EDSS but failed to link them to future EDSS and disability progression. Some studies documented a link between baseline serum NfL and baseline EDSS [ 243 , 269 , 289 , 297 , 311 ], while others did not find such a correlation [ 314 , 315 , 316 ]. In contrast, a few investigations could not reveal any association at all between CSF [ 40 , 157 , 266 , 317 ] or blood [ 272 ] NfL levels and EDSS.…”
Section: Fluid Biomarkers Of Multiple Sclerosiscontrasting
confidence: 65%
See 1 more Smart Citation
“…In summary, although there are relatively few studies on the relationship between blood neurofilament levels and the prognosis of ALS, blood neurofilament levels (NfL/pNfH) may be good predictive biomarkers of ALS patients; that is, higher blood neurofilament levels may be linked to faster DPR and higher risk of death in ALS patients. Although neurofilaments are not specific markers of ALS (e.g., neurofilaments are also promising biomarkers for multiple sclerosis, Alzheimer's disease, and Charcot-Marie-Tooth disease) (46)(47)(48), the predictive effect of neurofilaments on the prognosis of ALS patients suggests to some extent that the pathophysiological mechanism of ALS may be related to changes in the function and concentration of neurofilaments. Besides, neurodegenerative diseases are complex, and biomarkers are just one of the tools to help with diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that patients with more severe motor disability, short disease duration, and fatigue have a higher risk of worse quality of life (45). Thus, the relationship between PRO and blood biomarkers like CLP and sNfl should be investigated in larger, independent cohorts, since in other autoimmune diseases like IBD or multiple sclerosis, CLP and sNfl were shown to be a good predictor of health outcomes (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%